'The Crisis' as a journalistic frame in Romanian news media. (October 2014) - Vincze, Hanna Orsolya
The economic crisis and the policies proposed in response to it have held the attention of news media for many years. This article argues that the frequent use of the term 'crisis' as a catchphrase signals the presence of a journalistic frame, which possesses both generic and issue-specific features. The crisis-frame is analytically described along the four structural dimensions identified by Pan and Kosicki, using both content analytical arguments and close reading of characteristic passages. The crisis-frame is shown to have intersected with other local discursive constructs like the reform of the state or the problems of unemployment and migration. The article thus discusses substantive features of the news media of an Eastern European country, on which framing research is notoriously scarce. At the same time, it also contributes to the wider theoretical debate surrounding frame analysis, by describing how a media issue takes on generic features and becomes applicable to various topics and spheres of life.